2015
DOI: 10.1371/journal.pone.0127671
|View full text |Cite
|
Sign up to set email alerts
|

Foxp1 Regulates Cortical Radial Migration and Neuronal Morphogenesis in Developing Cerebral Cortex

Abstract: FOXP1 is a member of FOXP subfamily transcription factors. Mutations in FOXP1 gene have been found in various development-related cognitive disorders. However, little is known about the etiology of these symptoms, and specifically the function of FOXP1 in neuronal development. Here, we report that suppression of Foxp1 expression in mouse cerebral cortex led to a neuronal migration defect, which was rescued by overexpression of Foxp1. Mice with Foxp1 knockdown exhibited ectopic neurons in deep layers of the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 62 publications
4
54
0
Order By: Relevance
“…In addition, small groups of AmFoxP neurons were also seen in places comparable to the adult locations. This is consistent with the situation in vertebrates, where FoxP1 and FoxP2 orchestrate aspects of neural development (Rousso et al, ; Tsui, Vessey, Tomita, Kaplan, & Miller, ; Li et al, ; Ebisu et al, ) and are also expressed in adult tissue (Wohlgemuth, Adam, & Scharff, ). Moreover, FoxP2 is dynamically regulated in songbirds by singing and in mice by auditory experience (Miller et al, ; Horng et al, ; Teramitsu, Poopatanapong, Torrisi, & White, ; Thompson et al, ; Adam, Mendoza, Kobalz, Wohlgemuth, & Scharff, ).…”
Section: Discussionsupporting
confidence: 85%
“…In addition, small groups of AmFoxP neurons were also seen in places comparable to the adult locations. This is consistent with the situation in vertebrates, where FoxP1 and FoxP2 orchestrate aspects of neural development (Rousso et al, ; Tsui, Vessey, Tomita, Kaplan, & Miller, ; Li et al, ; Ebisu et al, ) and are also expressed in adult tissue (Wohlgemuth, Adam, & Scharff, ). Moreover, FoxP2 is dynamically regulated in songbirds by singing and in mice by auditory experience (Miller et al, ; Horng et al, ; Teramitsu, Poopatanapong, Torrisi, & White, ; Thompson et al, ; Adam, Mendoza, Kobalz, Wohlgemuth, & Scharff, ).…”
Section: Discussionsupporting
confidence: 85%
“…Using all vertebrate TRANSFAC (Matys et al, 2006) motifs with a p-value threshold of 10 -5 , we characterized TFBS that were only present in the human allele (98 TFBS) or only in the chimp allele (137 TFBS) ( Table S5). Some notable transcription factors that appear to have gained binding sites as a result of human substitutions in HAR enhancers are zinc finger proteins from the early growth response (EGR)1/2/3/4 families which play a role in neuronal plasticity (Liu et al, 2000;Knapska et al, 2004;Lu et al, 2011), POU1F1 which activates growth hormone genes (Sobrier et al, 2016), and FOXP1 which plays a role in radial migration and morphogenesis of cortical neurons and associated with autism and speech disorders (Li et al, 2015;Lozano et al, 2015;Teramitsu et al, 2004). It is worth noting that 2xHAR.548, one of our top scoring differentially active HARs (Table S3), is located within the topologically associating domain (TAD; (Dixon et al, 2012)) that encompasses FOXP1.…”
Section: Hars Contain Fixed Differences That Disrupt Tfbs Motifsmentioning
confidence: 99%
“…and FOXP1 during brain development, which suggests a possible effect of these transcription factors on a FTO-risk variant dependent on brain development mechanism. Supporting these data, in animal models it has been described that alterations in expression levels of these transcription factors (SP1, SP2 and FOXP1) have a direct effect reducing the morphogenesis of the brain (Li et al, 2015;Valin, Cook, Ross, Saklad, & Gill, 2009). Binding sites of SP1 and SP2…”
Section: Discussionmentioning
confidence: 76%
“…The in silico prediction analysis showed that FTO‐ risk variants could have a direct effect on modulating binding sites of transcription factors such as SP1 , SP2 and FOXP1 during brain development, which suggests a possible effect of these transcription factors on a FTO ‐risk variant dependent on brain development mechanism. Supporting these data, in animal models it has been described that alterations in expression levels of these transcription factors ( SP1 , SP2 and FOXP1 ) have a direct effect reducing the morphogenesis of the brain (Li et al., ; Valin, Cook, Ross, Saklad, & Gill, ). Binding sites of SP1 and SP2 were predicted to be disturbed by BD‐associated variants, and are transcription factors that play critical roles in embryonic and early development (Safe, Imanirad, Sreevalsan, Nair, & Jutooru, ).…”
Section: Discussionmentioning
confidence: 83%